Overuse injury induces persistent behavioral declines that correlate with higher IL-6 expression in the affected musculoskeletal tissues, circulation, and brain - Barbe, Mary F.; Lambi, Alex G.; Harris, Michele Y.; Patel, Parth R.; Tamas, Istvan P.; McGonagle, Elizabeth R.; Van Der Bas, Megan; Kalicharan, Betsy A.; Bright-Rowe, Lewis; Popoff, Steven N.; Klyne, David M. (Frontiers in Physiology, 2025)
BackgroundPain and sickness behaviors can be elicited by systemic inflammation. We sought to determine if mature rats displayed these behaviors following overuse injury and whether they correlated with inflammatory cytokines in musculoskeletal tissues, circulation, and the brain.MethodsMature female Sprague–Dawley rats were used: 26 controls and 41 rats trained across 6 weeks to pull at high force levels. Following training, 28 rats performed a high-repetition low-force task for 6 more weeks (task); the remaining rested (trained + rest). Behavioral data were collected at baseline, following training, and at study end. Tissues and serum were then collected and examined for the presence of inflammatory cytokines.ResultsFollowing training, task and trained + rest rats exhibited grip strength declines and forepaw sensitivity, compared to baseline and controls. Following task or rest, these behavioral changes persisted in addition to a reduction in social interactions (with juvenile female rats) in task rats, whereas trained + rest rats exhibited only low grip strength. Pro-inflammatory cytokines were elevated in serum and forelimb musculoskeletal and nerve tissues in task relative to control rats; IL-6 was elevated in serum and tissues in task relative to trained + rest rats. IL-6 immunostaining was observed in brain ependymal cells and cingulate cortex of task and trained + rest rats relative to control rats, and one circumferential blood brain region of task rats relative to the other groups. Higher cytokine levels in tissues often correlated with poorer behavioral responses.ConclusionThese data indicate that overuse injury induces inflammatory responses within the local/damaged tissues, circulation, and brain, which drives pain-related and sickness behaviors.